Mandatory Vaccination in Child Daycare and Its Relevance to COVID-19 - André den Exter (Portuguese Journal of Public Health, 2021)
Last month, the European Human Rights Court in Strasbourg made a landmark ruling on mandatory vaccination of children. After a long legal battle that lasted 16 years, the Grand Chamber decided, in the Vavricka case, that a Czech national law imposing a statutory duty of a set of standard vaccinations for children under the age of 15 does not violate the right to private life as protected under the European Convention on Human Rights (ECHR). Although the outcome of this ruling is not surprising, it may also have consequences relating to the controversy of mandatory COVID-19 vaccination which has been raised in other European countries.